Differences in pre-pregnancy diet quality by occupation among employed women. Issue 11 (26th August 2020) - Zaganjor, Ibrahim; Carmichael, Suzan L; Agopian, A J; Olshan, Andrew F; Desrosiers, Tania A; ,
Abstract: Objective: Maternal risk factors for pregnancy outcomes are known to vary by employment status. We evaluated whether pre-pregnancy diet quality varies by occupation in a population-based sample. Design: We analysed interview data from 7341 mothers in a national case–control study of pregnancy outcomes. Self-reported job(s) held during the 3 months before pregnancy were classified using Standard Occupational Classification (SOC) codes. Usual diet in the year before conception was assessed with a semi-quantitative FFQ and evaluated using the Diet Quality Index for Pregnancy (DQI-P). Using logistic regression, we calculated adjusted OR and 95 % CI to estimate associations between low diet quality (defined as the lowest quartile of DQI-P scores) and occupation types. Setting: The National Birth Defects Prevention Study: Arkansas, California, Georgia, Iowa, Massachusetts, North Carolina, New Jersey, New York, Texas, Utah. Participants: Employed mothers of infants born between 1997 and 2011. Results: No occupation was strongly associated with low diet quality. Moderate but relatively imprecise associations were observed for women employed in management (OR: 1·3; 95 % CI: 1·1, 1·7); arts, design, entertainment, sports and media (OR: 1·4; 95 % CI: 0·9, 2·1); protective service (OR 1·3; 95 % CI: 0·7, 2·5) and farming, fishing, and forestry occupations (OR: 0·5; 95 % CI: 0·2, 1·1). Conclusions: Our analyses suggest that women in certain occupations may have lower diet quality in the months before pregnancy. Further research is needed to determine whether certain occupations could benefit from interventions to improve diet quality in the workplace for women of reproductive age.